Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
The paper reviews the progress being made toward Indonesia's full emergence from the crisis. Banking sector restructuring has been at the heart of the reform program. Corporate debt restructuring is critical for resumption of normal credit flows and Indonesia's full and sustainable economic recovery. Finally, successive reform programs have aimed at alleviating the impact of the crisis on the poorest households and creating conditions for reversing the rise in poverty. Resuming Indonesia's long-term record of poverty reduction depends on effective social spending schemes and sustainable recovery.